Water quality assesment using NSF-WQI in the Bunter Lake, Pangkalan Baru Village, Siak Hulu Sub-district, Kampar Regency, Riau. - Arbi, Hidayatul; Fajri, Nur El; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractSeveral activities in the Bunter Lake contributed the input of organic and an-organic matter that affects the water quality, especially nutrient concentration in waters. A research aims to understand the trophic state of the Bunter Lake based on NSF-WQI has been conducted in August – September 2019. There were three stations namely Station I (inlet area), Station II (around the plantation area) and Station III (outlet area). Sampling were conducted 3 times, once/week. Water quality parameters measured were temperature, turbidity, NTU, TSS, pH, dissolved oxygen, BOD5, nitrate and total phospate. NSF-WQI are as follows: 51.38 – 52.68, the water quality parameters values are as follows: temperature: 28.7 – 30 oC, turbidity: 7.83 – 10.08 NTU, TSS: 19.7 – 28.7 mg/L, pH: 5, dissolved oxygen: 4.27 – 4.56 mg/L, BOD5: 8.14 – 8.72 mg/L, nitrate: 0.24 – 0.26 mg/L, total phospate: 1.19 – 1.62 mg/L. Based on NSF-WQI value, water quality of the Bunter Lake can be categorized as moderate to mesotrophic.Keywords :   Kampar River, Oxbow Lake, watersheed, mesotrophic